2020
DOI: 10.1136/bmjoq-2019-000788
|View full text |Cite
|
Sign up to set email alerts
|

Promoting appropriate utilisation of laboratory tests for inflammation at an academic medical centre

Abstract: To cite: Bartlett KJ, Vo AP, Rueckert J, et al. Promoting appropriate utilisation of laboratory tests for inflammation at an academic medical centre. BMJ Open Quality 2020;9:e000788.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Many studies combine several tools [ 14 , 17 , 19 ], which has been shown to have an additive effect on the overall outcome [ 20 ]. In addition, the collaboration of laboratory specialists and clinicians together with audits, feedbacks, reminders and multiple plan-do-study-act (PDSA) cycles will further improve efficiency in terms of a continuous improvement process [ 12 , 14 , 18 , 19 ].…”
Section: Possible Strategies To Avoid Inappropriate Test Utilizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies combine several tools [ 14 , 17 , 19 ], which has been shown to have an additive effect on the overall outcome [ 20 ]. In addition, the collaboration of laboratory specialists and clinicians together with audits, feedbacks, reminders and multiple plan-do-study-act (PDSA) cycles will further improve efficiency in terms of a continuous improvement process [ 12 , 14 , 18 , 19 ].…”
Section: Possible Strategies To Avoid Inappropriate Test Utilizationmentioning
confidence: 99%
“…Along with educational sessions, audits and feedback, Bartlett et al [ 14 ] introduced a panel for CRP and ESR testing. CRP was preselected, and an explanation referred to the recommended indications for these tests.…”
Section: Possible Strategies To Avoid Inappropriate Test Utilizationmentioning
confidence: 99%
See 3 more Smart Citations